Propuesta De Diseño Terminal De Transportes Mariquita-Tolima (2023)
The objective of the present investigation is to design an architectural proposal with optimal infrastructure, which responds to the needs of the population of Mariquita, with the purpose of providing an adequate space for land passenger transport activities which contributes to improving mobility and that in turn this helps the social-economic development of the municipality, solving the problems of arrival and departure of passengers, infrastructure and inter-municipal connectivity that currently occurs in the municipality of Mariquita; Being an architectural design that in turn seeks to improve the sensations and experiences of users through more comfortable spaces that allow preferential treatment and provide a more comfortable stay for users.